2021
DOI: 10.9734/ijecc/2021/v11i1130531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates, Tillage and Establishment Methods on Growth and Yield of Mustard

Abstract: This experiment was conducted at College Farm, Agricultural College, Polasa, Jagtial in Rabi, 2019-20. The experiment was laid out in strip-plot design with T1-Zero tillage with direct sowing, T2-Zero tillage with transplanting, T3-Conventional tillage with direct sowing and T4-Conventional tillage with transplanting in 4 horizontal strips and D1-15 November, D2-25 November and D3-5 December sowing dates in 3 vertical strips. Nursery was prepared 15 days earlier to sowing date for transplanting. Direct sowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Rana et al [34] reported that at 90% pod formation period, plant GDD, HTU and PTU requirements decreased with delay in sowing on different days. More GDD is required in early sowing to reach physiological maturity compared to late sowing and this may be owing to high temperatures during the late growing season, which forced the crop to mature [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Rana et al [34] reported that at 90% pod formation period, plant GDD, HTU and PTU requirements decreased with delay in sowing on different days. More GDD is required in early sowing to reach physiological maturity compared to late sowing and this may be owing to high temperatures during the late growing season, which forced the crop to mature [35][36][37].…”
Section: Discussionmentioning
confidence: 99%